2012
DOI: 10.1097/pec.0b013e318248b431
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Assessment of Reasons for Nonurgent Visits to the Emergency Department

Abstract: Guardians' concerns about perceptions of severity of illness in children and their schedules must be considered to effectively reduce nonurgent ED use, which may differ from the perceptions of professionals. Health professionals and systems seeking ways to decrease ED utilization may be able to better match capacity to demand both by increasing accessibility to primary care and by working to overcome guardians' perceptions that only EDs can handle acute illnesses or injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 17 publications
5
78
0
4
Order By: Relevance
“…There were multiple reasons why people felt accessing primary healthcare services was difficult. Anticipated waiting times for appointments and PCPs (including GPs) being busy were key factors,40, 41, 42 with one study reporting that 44% of patients found their GP “inaccessible to their needs.” This was also linked to patient perceptions around accessibility and availability of appointments at times of day that were convenient to patients,43 limited PCP opening hours,44 with a small proportion of patients reporting that they were unable to obtain a PCP appointment 38. Lack of primary health service available after hours was raised by one study 18.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were multiple reasons why people felt accessing primary healthcare services was difficult. Anticipated waiting times for appointments and PCPs (including GPs) being busy were key factors,40, 41, 42 with one study reporting that 44% of patients found their GP “inaccessible to their needs.” This was also linked to patient perceptions around accessibility and availability of appointments at times of day that were convenient to patients,43 limited PCP opening hours,44 with a small proportion of patients reporting that they were unable to obtain a PCP appointment 38. Lack of primary health service available after hours was raised by one study 18.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases anxiety was due to worries about the legitimacy of need,39 with patients not wishing to use services inappropriately. There was a strong sense that patients viewed their conditions to be serious 40, 42, 43, 48, 55, 56, 57. This was juxtaposed with evidence that patients were not always capable of assessing which health problems required emergency care and were sometimes unsure of the legitimacy of their health needs 39, 58…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Other investigators have observed that factors motivating parents to seek ED care for their infants include the perceived severity of their infant' s illness and the difficulty accessing timely primary care. 28 If it is found that many ED visits for these infants are truly for "assessment" or "parental education" only (without receipt of medications or testing of any kind) then it may be imperative for the medical community to develop strategies to provide improved parental education and convenient access to alternative care venues.…”
Section: Discussionmentioning
confidence: 99%